2022
DOI: 10.3390/ani12131689
|View full text |Cite
|
Sign up to set email alerts
|

Velvet Antler Production and Hematological Changes in Male Sika Deers Fed with Spent Mushroom Substrate

Abstract: At present, spent mushroom substrate (SMS) is a waste resource that is producing a pollution problem in China, and which has some use as animal feed or fertilizer, has not been assessed as a feed for deer. The purpose of this study is to expand the feed of male sika deer and reduce the feeding cost by using the waste resource of SMS. The 10% concentrated supplement was replaced with SMS and the feed intake, apparent digestibility, blood index and velvet production of male sika deer were measured. As the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…All sika deer lived in the artificial feedlot without weeds, shrubs, trees, etc. According to our previous study [ 16 ], the control group was fed normally and the experimental group was fed with corncob SMS-MP (dried), replacing 10% of the concentrate supplement. The diets were restricted and offered 3 times per day at 4:30~5:30, 10:30~11:30, and 16:30~17:30.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All sika deer lived in the artificial feedlot without weeds, shrubs, trees, etc. According to our previous study [ 16 ], the control group was fed normally and the experimental group was fed with corncob SMS-MP (dried), replacing 10% of the concentrate supplement. The diets were restricted and offered 3 times per day at 4:30~5:30, 10:30~11:30, and 16:30~17:30.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, reducing the cost of raising sika deer is an important research direction to expand the deer industry. Our previous study has shown that 10% of SMS-MP can be safely replaced with a concentrated supplement in male sika deer with no adverse effects on nutrient digestion and hematology [ 16 ]. The purpose of this study was to evaluate the effectiveness of SMS-MP replacing 10% concentrate supplementation on the hematology and digestion in sika doe and the hematology of suckling fawn, reducing feeding costs while avoiding the environmental pollution of SMS-MP.…”
Section: Introductionmentioning
confidence: 99%
“… Origin of SMS SMS content in fibers and crude protein Animals in feeding trials Type of feed, inclusion levels, and length of feeding trials Main outcome Ref. NFD, ADF and ADL (%) Crude fiber (%) Protein (%) Pleurotus sajor-caju 60.3, 52.3, 4.1 NR 9.3 Alpine dairy goats Rice straw fermented with P. sajor-caju SMS (5:1 w/w for 8 weeks), diet and water provided ad libitum , 28 days SMS effectively improved the nutrient content, availability in the rumen, and feeding value of rice straw; increased effective degradability of dry mater and fibers in the rumen; improved intake and milk yield [ 61 ] Pleurotus ostreatus NR NR 3.0 Male Sika deers SMS (10%), 60 days SMS led to reduction in the intake of organic matter, and improved digestibility of crude fat [ 62 ] Flammulina velutipes NR NR 5.1 Νo effect on apparent nutrient digestibility, feed intake, velvet antler production, or biochemical indexes P. ostreatus NR NR NR Liuyang black goats SMS co-fermented with feed and whole plant rice, 60 days Feeding with co-fermented whole plant rice and SMS had no adverse effect on the slaughter performance, while the meat quality was improved [ 63 ] Cordyceps militaris NR NR NR Crossbred growing pigs SMS (0.2%, w/w), 6 weeks …”
Section: Spent Mushroom Substrate As Feedmentioning
confidence: 99%
“…Feeding male sika deer for 60 days with P. ostreatus SMS (10%, w/w) resulted in a reduction of the intake of organic matter and improved digestibility of crude fibers, while no effect on either the apparent nutrient digestibility, feed intake, velvet antler production, or biochemical indexes was observed when F. velutipes SMS (10%, w/w) was fed to the same animals [ 62 ]. When hot water extracts from G. lucidum and Ganoderma chalceum (syn.…”
Section: Spent Mushroom Substrate As Feedmentioning
confidence: 99%
“…Beyond ruminants, SMS integration into livestock, poultry, and fish diets enhances microbial balance and promotes growth [7]. SMS's potential as a feed source is evident in various species [14], including insects (Beetle: Protaetia Brevitarsis; Mealworm: Tenebrio molitor) [15,16], rabbits (Cuban Brown: Oryctolagus cuniculus) [17], pigs (Sus scrofa domesticus) [18], and ruminants (Sika deer: Cervus nippon, Dairy cows: Bos taurus coreanae, Bos taurus) [19][20][21]. Similarly, to mushrooms' fruiting bodies, whose biological activity is far more studied, SMS can exhibit nutraceutical properties worth studying, such as antioxidant capacity [22][23][24], antibacterial and antifungal activity [25][26][27], antiaging activity [28], and other health benefits [29].…”
Section: Introductionmentioning
confidence: 99%